Ethe Role of BNNK Ciamis in the P4GN Program as an Effort to Protect Self-Protection of RA, MI, MTS, and SMA Students: A Review of Islamic Counseling Guidance - Irwan Bagus Setiawan; Yandi Cahya Yundani; Didin Solehuddin (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2026)
This study aims to analyze the role of the Ciamis Regency National Narcotics Agency (BNNK) in implementing the Prevention and Eradication of Drug Abuse and Illicit Trafficking (P4GN) program as a self-protection effort for students at the RA, MI, MTs, and SMA levels from the perspective of Islamic Counseling Guidance. The research method used was qualitative with a descriptive approach, through observation, documentation, and literature review. The results indicate that the Ciamis BNNK plays a strategic role through educational programs such as the Anti-Narcotics Curriculum Integration (IKAN), school counseling, and the Desa Bersinar program. From the perspective of Islamic Counseling Guidance, the approach used integrates psychological and spiritual aspects, such as humanistic, behavioristic, and client-centered approaches. This program has been proven to increase students’ awareness of the dangers of drugs and foster self-resilience based on Islamic values